Terapi Maksimal Medikamentosa pada Rinosinusitis Kronis - Vita Kusumawijaya; Yoan Levia Magdi (Conferences of Medical Sciences Dies Natalis, 2019)
Chronic rhinosinusitis (CRS) is a group of symptoms and signs that can be caused by a variety of different etiologies. Continuous inflammation of the mucosa and thick mucus often causes symptoms of post nasal drip, nasal congestion, also decrease the sense of smell along with facial tenderness. The exact etiology of chronic rhinosinusitis is still unknown and is multifactorial, and there is no exact single molecular mechanism that explains injury from tissue changes. Maximum medical therapy (MMT) is a standard of care for chronic rhinosinusitis care before recommendations for surgery. The chosen therapy regimen varies for each individual where the duration of inflammation is related to the duration of use of maximal pharmacologic therapy. The main type of medical therapy used for chronic rhinosinusitis consists of antibiotics, corticosteroids, and nasal irrigation. MMT is useful in reducing the symptoms and complaints of patients, and helps to facilitate the success of operations performed, that will have an impact on quality of life and socioeconomic aspects.